2020
DOI: 10.1016/j.ihj.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Role of routine fetal echocardiography in an unselected group of pregnant women for prenatal detection of cardiac malformations

Abstract: Objectives We investigated the potential for improvement in prenatal detection of congenital heart disease (CHD) by routinely performing detailed fetal echocardiography (FE) in all pregnant women. Methods Following routine obstetric sonography, 1445 unselected pregnant women were prospectively subjected to FE at gestational ages between 16 and 24 weeks, or at first visit, if they presented later. Maternal or fetal factors, conventionally known to be associated with risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…By contrast, a study from India in which 1445 unselected pregnant women who were prospectively subjected to FE between 16 and 24 weeks of gestation or at first visit demonstrated that FE has a high sensitivity and specificity in detecting CHD, recommending that it should be done in every pregnancy. The overall prevalence of CHD in that study was found to be 8.3/1000 (12 had CHD, with cardiac tumors and patent ductus arteriosus being identified among the cardiac anomalies detected) 21 . In the present study, the anomalies detected were hypoplastic left heart syndrome, pulmonary stenosis, cardiac tumor, absent Doppler, and supraventricular tachycardia.…”
Section: Discussionsupporting
confidence: 44%
“…By contrast, a study from India in which 1445 unselected pregnant women who were prospectively subjected to FE between 16 and 24 weeks of gestation or at first visit demonstrated that FE has a high sensitivity and specificity in detecting CHD, recommending that it should be done in every pregnancy. The overall prevalence of CHD in that study was found to be 8.3/1000 (12 had CHD, with cardiac tumors and patent ductus arteriosus being identified among the cardiac anomalies detected) 21 . In the present study, the anomalies detected were hypoplastic left heart syndrome, pulmonary stenosis, cardiac tumor, absent Doppler, and supraventricular tachycardia.…”
Section: Discussionsupporting
confidence: 44%
“…While another study from Northern India found incidence of CHD as 15 per 1000. 12,13 In a recent study by Qiu X and coworkers 14 evaluated fetal echocardiography of 67,834 pregnant women in which 1492 fetuses were found to have CHD. Prenatal genetic examination on amniotic fluid and cord blood, revealed chromosomal abnormalities in 20.43% of foetuses with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…While another study from Northern India found incidence of CHD as 15 per 1000. 12,13 In a recent study by Qiu X and coworkers 14 evaluated fetal echocardiography of 67,834 pregnant women in which 1492 fetuses were found to have CHD. Prenatal genetic examination on amniotic fluid and cord blood, revealed chromosomal abnormalities in 20.43% of foetuses with CHD.…”
Section: Discussionmentioning
confidence: 99%